FATE OF THE MESOSOMES OF BACILLUS MEGATERIUM DURING PROTOPLASTING - Fitz-James, Philip (1964)
Fitz-James, Philip (University of Western Ontario, London, Canada). Fate of the mesosomes of Bacillus megaterium during protoplasting. J. Bacteriol. 87:1483–1491. 1964.—When cells of Bacillus megaterium growing rapidly in peptone medium are treated with sucrose buffer prior to protoplasting, their membranous organelles or mesosomes are extruded as a collection of vesicles into the wall-membrane interspace. On subsequent protoplast formation with lysozyme digestion, the mesosome remnants become dispersed. If glucose is added to the peptone, a slightly more persistent mesosome can be seen and photographed by phase microscopy during lysozyme digestion, either as a wall-attached granule or as a protoplast tag. In thin section, mesosomes are found as small, variably dispersed aggregates of vesicles and wall-like material. Complete protoplasts are usually free from internal mesosomes but may contain twists or everted pockets of membrane on their periphery. By lysozyme digestion of partially fixed cells, the empty mesosome pockets in the membrane can be demonstrated in rod-shaped protoplasts.